Characterization of allele-specific expression of the X-linked gene MAO-A in trophectoderm cells of bovine embryos produced by somatic cell nuclear transfer - Ferreira, A. R. [UNESP]; Aguiar Filho, L. F. C.; Sousa, R. V.; Sartori, R. [UNESP]; Franco, M. M. (Funpec-editora, 2015)
Somatic cell nuclear transfer (SCNT) may affect epigenetic mechanisms and alter the expression of genes related to embryo development and X chromosome inactivation (XCI). We characterized allele-specific expression of the X-linked gene monoamine oxidase type A (MAO-A) in the trophectoderm (TF) of embryos produced by SCNT. Total RNA was isolated from individual biopsies (N = 25), and the allele-specific expression assessed by reverse transcription-polymerase chain reaction-restriction fragment length polymorphism. Both paternal and maternal alleles were expressed in the trophectoderm. However, a higher frequency of the mono-allelic expression of a specific allele was observed (N = 17; 68%), with the remaining samples showing the presence of mRNA from both alleles (N = 8; 32%). Considering that MAO-A is subject to XCI in bovine, our results suggest that SCNT may influence XCI because neither an imprinted (mono-allelic expression in all samples) nor a random (presence of mRNA from both alleles in all samples) pattern of XCI was observed in TF. Due to the importance of XCI in mammalian embryo development and its sensitivity to in vitro conditions, X-linked genes subject to XCI are candidates for use in the development of embryo quality molecular markers for assisted reproduction.
Keywords: Cloning; Trophectoderm; MAO-A; X chromosome inactivation